Designed growth of porous 2D Nb2O5 with Ag nano-particles for differential detection of UV-A and UV-C - Lee, Sang Hoon; Kim, Bum Jun; Nasir, Tuqeer; Choi, Ik Jun; Jeong, Byung Joo; Woo, Chaeheon; Lim, Hyung Kyu; Kim, Youngho; Nanda, Sitansu Sekhar; Yi, Dong Kee; Yu, Hak Ki; Choi, Jae Young (Nanotechnology, 2020)
We demonstrate the differential detection of UV-A (ultra-violet 320-400 nm region) and UV-C (100-280 nm) using porous two-dimensional (2D) Nb2O5 and additional Ag nano-particle decoration. The 2D Nb2O5, which has band-absorption edge near the UV-A zone, was synthesized by thermodynamic conversion of 2D material NbSe2 (Nb2O5 has lower Gibbs formation energy than NbSe2). For the differential detection (to distinguish with UV-C absorption), we decorated the Ag nano-particles on the Nb2O5 surface. By coating Ag nano-particles, we can expect (i) a decrease in the area of light absorption by the Ag-coated area, and (ii) an increase of surface plasmon absorption by Ag nano-particles, especially the UV-A region, resulting in strong intensity ratio change UV-A/UV-C.
Keywords: Absorption edges; Differential detection; Formation energies; Intensity ratio; Surface plasmon absorption; Two Dimensional (2 D); Ultra violet; Nb2O5 nano-plates; NbSe2; thermodynamic conversion; UV sensors